Room air conditioning performance using liquid-suction heat exchanger retrofitted with R290. (March 2019) - Nasution, Dian Morfi; Idris, Muhammad; Pambudi, Nugroho Agung; Weriono,
Abstract: In this paper, a study of room air conditioning performance when using a liquid-suction heat exchanger retrofitted with R290 has been carried out with the aim of determining the influence of LSHX and R290 in terms of refrigeration effect, power consumption, COP, and heat exchanger effectiveness. A liquid-suction heat exchanger (LSHX) with length of 178 mm was designed and installed in air conditioning pipelines. The RAC used is a split-type with input power of 395 W and initial refrigerant R22. The experiment was conducted on two system conditions with 6 tests each. The results showed that LSHX provides an advantage in improving the energy efficiency of the standard RAC systems. Energy savings and increased COP can be as much as 27.69% and 38.29%. The adoption of R290 also helps reduce the potential of ozone depletion and global warming. It can be concluded that the combination of LSHX and R290 can produce better performance.